(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article highlights the problems of socialization of children with special needs in the family and outside the family through the organization of various forms of socio-cultural activities and effective adaptation practices that create conditions for the formation and development of their active life position.